The well-grounded Python developer : how the pros use Python and Flask - Farrell, Doug (Manning Publications, 2023)
If you’re new to Python, it can be tough to understand when, where, and how to use all its language features. This friendly guide shows you how the Python ecosystem fits together, and grounds you in the skills you need to continue your journey to being a software developer. The Well-Grounded Python Developer builds on Python skills you’ve learned in isolation and shows you how to unify them into a meaningful whole. It helps you understand the dizzying array of libraries and teaches important concepts, like modular construction, APIs, and the design of a basic web server. As you work through this practical guide, you’ll discover how all the bits of Python link up as you build and modify a typical web server application—the kind of web app that’s in high demand by modern businesses.